Analyzing soccer dynamics using the motion in mind model - Muhammad Numan,; Iida, Hiroyuki; Mohd Nor Akmal Khalid, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In soccer, understanding both the overall dynamics of the game and team performance is crucial for developing effective strategies and enhancing overall success. This study employs the Motion in Mind (MiM) model to analyze the dynamics of soccer and teams’ performance, with a particular focus on the FIFA World Cup 2022. The objective is to understand how different phases (opening, middlegame, and endgame) of a soccer sport are influenced by the key performance matrices such as total attempts and goals, as well as strategic adaptations by teams. Utilizing data from 64 matches involving 32 teams, we applied a phase-specific analysis to examine metrics such as velocity, mass, acceleration, force, potential energy, and momentum. The findings reveal distinct performance patterns across the game phases: the opening phase is characterized by higher challenges and uncertainties, the middlegame phase shows improved success rates and strategic adaptations, and the endgame phase highlights optimal performance levels with peak velocity and strategic efficiency. The study also provides a comparative analysis of Argentina and France, identifying key factors that contributed to Argentina's victory. These insights enhance the understanding of competitive sports dynamics and suggest practical applications for improving team strategies and performance in future tournaments.